Noun-it-right snake and ladder board game: learning about nouns – an enhancement tool in the teaching of grammar / Aishah Musa, Nur Afifah Ariffin and Asrol Hasan - Musa, Aishah; Ariffin, Nur Afifah; Hasan, Asrol (Universiti Teknologi MARA, Kedah, 2016)
Learning English is not an easy task especially when it comes to learning grammar. One way to achieve this is through using games. Due to the numerous benefits that games provide, the Noun- it-Right Snake and Ladder Game: Learning about Nouns was created. This study was conducted to determine whether the usage of this board game is able to improve the teaching and learning of grammar. The study was carried out among Standard 5 pupils in a primary school in Kedah. The data for the study was analysed using the paired-sample T test. The findings of the study suggested that the usage of this board game has helped the students understand nouns better.